Le colonel Kadhafi en France, ou le pari méditéranéen - Pierre Beckouche (EchoGéo)
The recent visit of Muammar Kadhafi in Paris cannot be understood only through the classic dilemma between economic interests and political morality. The actual framework is the Mediterranean Union, in order to relaunch the Barcelona process. There are two difficulties: European countries have to be convinced, were they Mediterranean (Italy, Spain) or not (Germany); south Mediterranean neighbours have to rally, in order to enter an era of truly equal partnership with Europe.